2023
DOI: 10.3390/jmmp7060191
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Laser Surface Modification on AISI 301LN Steel: A Micro-Mechanical Study

Mohammad Rezayat,
Antonio Mateo,
Joan Josep Roa

Abstract: This article investigates the surface hardening capability of a metastable austenitic TRansformation Induced Plasticity (TRIP) stainless steel, particularly on AISI 301LN, by laser texturing. This technology produces microstructural surface changes in terms of both phase transformation and grain size modification and, as a direct consequence, the laser influences the surface characteristics, mainly hardness and roughness. In this sense, the key parameters (laser power, scanning speed and position of the focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The aim was to develop a mathematical model that accurately represented the relationship between the response and input variables with the least amount of error [25]. There are various Design of Experiments (DOE) methods available, depending on the type of input variable parameters studied [36]. The current study used Response Surface Methodology (RSM) as the design method, which combines statistical methods and applied mathematics to analyze output variables that are influenced by multiple independent input variables.…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…The aim was to develop a mathematical model that accurately represented the relationship between the response and input variables with the least amount of error [25]. There are various Design of Experiments (DOE) methods available, depending on the type of input variable parameters studied [36]. The current study used Response Surface Methodology (RSM) as the design method, which combines statistical methods and applied mathematics to analyze output variables that are influenced by multiple independent input variables.…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…Investigating key parameters such as laser power, scanning speed, and focal length position, the study reveals that maximum surface hardening is achieved by increasing laser power and decreasing scanning speed. A regression equation correlates processing parameters with resulting surface integrity, emphasizing the influence of laser patterning on mechanical properties [32]. Dywel et al have shown that LST using a pulsed Nd:YAG laser can significantly reduce the friction coefficient and wear rate in AISI 304 and 316 stainless steel [33].…”
Section: Introductionmentioning
confidence: 99%